Growth performance of white seabass (Lates calcarifer) cultivated using recirculation aquaculture system (RAS) - Sahusilawane, Helena Afia; Metungun, Jacomina; Fitrinawati, Henny; Kilmanun, Juliana Ester (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2024)
White seabass (Lates calcarifer) is classified as a fishery commodity that has a high selling value with an easy cultivation method. However, water quality is an obstacle in the fish cultivation process. Therefore, it is necessary to implement an appropriate cultivation system, including a recirculation aquaculture system (RAS). RAS is reuse of water that has been used through a filter so that fish with high growth and survival are obtained. The aim of the research was to analyze the growth performance of white seabass cultivated with RAS. The research was conducted at the Mariculture Laboratory of the Aquaculture Technology Study Program, Tual State Polytechnic of Fisheries in June to August 2024. The research was used a descriptive type with initial length measurements (4 and 5 cm) and was repeated 3 times. A total of 10 fish were kept in a hapa in a rearing tank and equipped with RAS using sand and charcoal filters. Growth performance were measured included body length, body weight, growth rate, and survival rate. The research results show that the RAS system determines the growth performance of white seabass. This is evidenced by the increasing average increase in length and body weight. At an initial length of 4 cm, the average increase was 6.5 cm and 4.25 g, while at an initial length of 5 cm it was 8.3 cm and 6.5 g. The average survival rate was 75% at an initial fish size of 4 cm and 86% at an initial fish size of 5 cm. Thus, the RAS system can be applied in white seabass cultivation.